2022
DOI: 10.1093/ajcn/nqac153
|View full text |Cite
|
Sign up to set email alerts
|

A single, high-fat meal adversely affects postprandial endothelial function: a systematic review and meta-analysis

Abstract: Background Endothelial dysfunction is a predictive risk factor for the development of atherosclerosis and is assessed by flow-mediated dilation (FMD). Although it is known that nitric oxide-dependent endothelial dysfunction occurs after consuming a high-fat meal, the magnitude of the effect and the factors that affect the response are unquantified. Objectives To conduct a systematic review and meta-analysis exploring the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 176 publications
1
7
0
Order By: Relevance
“…The reason for such decline is not entirely clear, but it is suggested to relate to younger individuals, men, and those with baseline hyperglycemia as well as high fasting FMD (12). Interestingly, this is consistent with recent work reporting that high-fat meals result in a reduction of 1% FMD at 2-, 3-, and 4-h postingestion ( P < 0.01), with a higher amount of fat intake and energy related to declines in endothelial function at only 3 and 4 h postingestion, respectively (13). Because meal ingestion can impact NO bioavailability (12), it is important to understand the impact of nutrients surrounding exercise to optimize vascular function.…”
Section: Does Macronutrient Composition Modulate Exercise Effects On ...supporting
confidence: 92%
See 1 more Smart Citation
“…The reason for such decline is not entirely clear, but it is suggested to relate to younger individuals, men, and those with baseline hyperglycemia as well as high fasting FMD (12). Interestingly, this is consistent with recent work reporting that high-fat meals result in a reduction of 1% FMD at 2-, 3-, and 4-h postingestion ( P < 0.01), with a higher amount of fat intake and energy related to declines in endothelial function at only 3 and 4 h postingestion, respectively (13). Because meal ingestion can impact NO bioavailability (12), it is important to understand the impact of nutrients surrounding exercise to optimize vascular function.…”
Section: Does Macronutrient Composition Modulate Exercise Effects On ...supporting
confidence: 92%
“…This is consistent with others highlighting variation in response to exercise for endothelial function, glucose control, as well as blood pressure (10), with some reporting an intensity/duration dose response on endothelial improvements (4,11). Many of these exercise studies though do not strictly control diet, and this could be problematic for exercise adaptation because hyperglycemia, as well as dyslipidemia impair endothelial function (1,12,13). Given that work has shown energy deficit postexercise may influence metabolic insulin sensitivity and inflammation, we present the novel hypothesis that variations in energy intake surrounding exercise might alter endothelial adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Postprandial endothelial dysfunction is a clinically important condition and has been reported following high-fat meals in both healthy subjects and in those with risk factors for CVD. Postprandial endothelial dysfunction has been proposed to be triggered through oxidative stress induced by hypertriglyceridemia, where NO bioavailability is reduced by the superoxide anion (O 2 − ), resulting in the generation of the highly reactive and cytotoxic peroxynitrite [109][110][111]. In overweight adults with high triglyceride plasma levels and waist circumference measurements, L-arginine supplementation was able to overcome cardiovascular risk factors following 4.5 g supplementation for 4 weeks, where an inhibition of the decrease in postprandial endothelial function induced by a high-fat meal was observed, demonstrated by a 29% reduction in FMD when compared to a 50% reduction in FMD in placebo-treated subjects.…”
Section: L-argininementioning
confidence: 99%
“…In addition, after a high fat meal, there is an increase in plasma oxidative stress markers, [6] such as lipid hydroperoxides and isoprostanes [7] and in endothelial dysfunction. [8] However, a systematic review concluded that there was limited evidence for postprandial inflammation, except that IL−6 increased consistently even in healthy volunteers, [9] although this issue is still contentious. [10][11][12][13] These examples indicate that postprandial responses are complex and incompletely understood.…”
Section: Introductionmentioning
confidence: 99%